Parathyroid hormone attenuates osteoarthritis pain by remodeling subchondral bone in mice - Qi Sun; Gehua Zhen; Tuo Peter Li; Qiaoyue Guo; Yusheng Li; Weiping Su; Peng Xue; Xiao Wang; Mei Wan; Yun Guan; Xinzhong Dong; Shaohua Li; et al. (eLife, 2021)
Osteoarthritis, a highly prevalent degenerative joint disorder, is characterized by joint pain and disability. Available treatments fail to modify osteoarthritis progression and decrease joint pain effectively. Here, we show that intermittent parathyroid hormone (iPTH) attenuates osteoarthritis pain by inhibiting subchondral sensory innervation, subchondral bone deterioration, and articular cartilage degeneration in a destabilized medial meniscus (DMM) mouse model. We found that subchondral sensory innervation for osteoarthritis pain was significantly decreased in PTH-treated DMM mice compared with vehicle-treated DMM mice. In parallel, deterioration of subchondral bone microarchitecture in DMM mice was attenuated by iPTH treatment. Increased level of prostaglandin E2 in subchondral bone of DMM mice was reduced by iPTH treatment. Furthermore, uncoupled subchondral bone remodeling caused by increased transforming growth factor β signaling was regulated by PTH-induced endocytosis of the PTH type 1 receptor–transforming growth factor β type 2 receptor complex. Notably, iPTH improved subchondral bone microarchitecture and decreased level of prostaglandin E2 and sensory innervation of subchondral bone in DMM mice by acting specifically through PTH type 1 receptor in Nestin+ mesenchymal stromal cells. Thus, iPTH could be a potential disease-modifying therapy for osteoarthritis.